2020
DOI: 10.3389/fphys.2020.01023
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Repeated-Sprint Training in Hot and Cool Conditions Similarly Benefits Performance in Team-Sport Athletes

Abstract: This study compared the performance and physiological adaptations of short-term repeated-sprint training in HOT [40°C and 40% relative humidity (RH)] and COOL (20°C and 40% RH) conditions in team-sport athletes. Twenty-five trained males completed five training sessions of 60 min over 7 days in HOT (n = 13) or COOL (n = 12) conditions, consisting of a submaximal warm-up and four sets of maximal sprints. Before and after the intervention, intermittent shuttle running performance was assessed in cool and repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Nevertheless, 6 wk of local heat therapy on plantarflexors (i.e., 8 h·d −1 using heat pads, 5 d·wk −1 ) induced no effect on strength and contractile properties of plantarflexors in active participants (44). Active short-term HA also showed no effect on knee extensor maximal force and VA (45). Recent studies also showed that adding local repeated heat stress during a long period (i.e., 10–12 wk) of resistance training had no effect on muscle strength production (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, 6 wk of local heat therapy on plantarflexors (i.e., 8 h·d −1 using heat pads, 5 d·wk −1 ) induced no effect on strength and contractile properties of plantarflexors in active participants (44). Active short-term HA also showed no effect on knee extensor maximal force and VA (45). Recent studies also showed that adding local repeated heat stress during a long period (i.e., 10–12 wk) of resistance training had no effect on muscle strength production (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Gale, Etxebarria, Pumpa, and Pyne (2020) demonstrated that the six repeated‐sprint training sessions in 34°C over 12 days resulted in an 8–13% greater improvement in running capacity, while HA was unaffected. The five repeated‐sprint training over 7 days under heat stress in 40°C elicited partial heat adaptation, in turn improved running distance during the Yo‐Yo IR1 Tests (Périard et al, 2020). Altogether, it appears the threshold required for heat adaptation via repeated‐sprint training is higher than the threshold needed for improvements in aerobic fitness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, short‐term training in thermoneutral environments led to improvements in aerobic performance; however, it did not elicit heat adaptation (Cheung & McLellan, 1998; McGarr, Hartley, & Cheung, 2014). Previous study utilizing short‐term repeated‐sprint training (total 300 min) in 40°C have demonstrated evidence of enhancement of endurance performance and attainment of partial heat adaptation (Périard et al, 2020). In this study, total exposure time during the short‐term HA training was 410 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation